Molecular docking study of 3,6 bis(3’substituted propoxy) and 3,6 bis (5’substituted pentyloxy) xanthone derivatives as PGHS- 2 inhibitors - Aparoop Das, Pratap Parida, Neha Agarwal, Jaya shree, Brajesh Shankar and Dipankar Chakraborty (Journal of Applied Pharmaceutical Science, 2013)
The primary effect of the NSAIDs is to inhibit cyclooxygenase (COX or prostaglandin synthase), thereby impairing the ultimate transformation of arachidonic acid to prostaglandins, prostacyclin, and thromboxanes. Two related isoforms of the COX enzyme have been described, COX-1 and COX-2. Identification of this cyclooxygenase-2 (COX-2) isoform resulted in the development of selective COX-2 inhibitors, with the hope of producing a safer analgesic and anti-inflammatory agent. The principal benefit with the selective COX-2 inhibitors is the production of comparable analgesia and antiinflammatory effects to the nonselective NSAIDs, but with fewer symptomatic gastric and duodenal ulcers and a decrease in gastrointestinal symptoms. In the present work, twelve novel series of xanthone derivatives (A1-A6 and B1-B6) were allowed to dock against PGHS-2(prostaglandin endoperoxide synthase-2) protein (PDB ID: 3LN1) to evaluate their comparative efficacy in terms of docking performance. The results are discussed on the basis of binding energy value.
Keywords: Xanthone derivatives, PGHS-2, Autodock 4.2, Exome Ho